MODEL PELAYANAN PENYERAHAN FASILITAS UMUM DAN FASILITAS SOSIAL DARI PENGEMBANG PERUMAHAN KE PEMERINTAH KOTA MAKASSAR - Alam Tauhid Syukur; Ady Hermawansyah; Nielma Palamba; Hari Hari (Jurnal Inovasi dan Pelayanan Publik Makassar, 2019)
This study seeks to find a service model for the delivery of public facilities and social facilities from housing developers to the Makassar Municipality Government. Descriptive qualitative research design that aims to find data and information about service delivery of public facilities and social facilities from housing developers to the Municipality Government of Makassar. The results of this study indicate that the process of handing over public facilities and social facilities from the developer to the Makassar Municipality Government has not been optimal. Regulation of the Minister of Home Affairs Number 9 of 2009 concerning Guidelines for the Delivery of Infrastructure, Facilities and Utilities in Regional Housing and Settlements. Then the related OPD works partially and can have a sectoral ego. And there are still a number of public facilities and social facilities that have not been recorded as regional assets because there is no official report or documents that do not meet the basic requirements for recording of social and public health facilities and are yet clear according to the demand for assets.